2013
DOI: 10.1007/s13187-013-0459-z
|View full text |Cite
|
Sign up to set email alerts
|

A Peer-Led Decision Support Intervention Improves Decision Outcomes in Black Women with Breast Cancer

Abstract: Previous reports suggest that Black breast cancer patients receive less patient-centered cancer care than their White counterparts. Interventions to improve patient-centered care (PCC) in Black breast cancer patients are lacking. Seventy-six women with histologically confirmed breast cancer were recruited from the Washington, DC area. After a baseline telephone interview, women received an in-person decision support educational session led by a trained survivor coach. The coach used a culturally appropriate gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 17 publications
(24 reference statements)
1
43
0
Order By: Relevance
“…Rather than having a direct effect on outcomes, contextual factors such as collectivism (which was significant in bivariate analysis) may serve as mediators or moderators of anxiety or depression. Contextual factors such as spirituality and collectivism have been successfully integrated into interventions to improve self-efficacy regarding treatment decisions and communication with providers in newly diagnosed Black patients [29,30,53]. A strong patient-provider relationship after diagnosis may help reduce distress in Black patients with higher levels of medical mistrust.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than having a direct effect on outcomes, contextual factors such as collectivism (which was significant in bivariate analysis) may serve as mediators or moderators of anxiety or depression. Contextual factors such as spirituality and collectivism have been successfully integrated into interventions to improve self-efficacy regarding treatment decisions and communication with providers in newly diagnosed Black patients [29,30,53]. A strong patient-provider relationship after diagnosis may help reduce distress in Black patients with higher levels of medical mistrust.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of cancer care, a 2008 systematic review indicated that patients exposed to DAs were more likely to participate in decision making and to achieve higher quality decisions . Additional studies indicated that DAs increased cancer patients' knowledge, participation in decision making, self‐efficacy in communicating with the provider and in making treatment decisions, and decisional satisfaction . DAs can also reduce cancer patients' stress or anxiety and decisional conflict .…”
Section: Methodsmentioning
confidence: 99%
“…Satisfaction with the nutritionist, exercise physiologist, and survivor coach was assessed with Likert-formatted items respectively that captured participants' ratings of their performance, interpersonal, and technical skills [36]. Higher scores represented higher levels of satisfaction.…”
Section: Study Design and Intervention Armsmentioning
confidence: 99%